2017
DOI: 10.1111/jdv.14488
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and management of male genital lichen sclerosus: a retrospective review of 301 patients

Abstract: Introduction Male genital lichen sclerosus (MGLSc) is an acquired, chronic, inflammatory skin disease that is associ-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 20 publications
5
94
0
1
Order By: Relevance
“…This is in stark contrast to non‐obese men who are circumcised for refractory lichen sclerosus. Circumcision is generally curative in these men, and we have seen no cases of SCC in the MGLSc patients diagnosed and treated in our subspecialty clinics over the last 20 years …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in stark contrast to non‐obese men who are circumcised for refractory lichen sclerosus. Circumcision is generally curative in these men, and we have seen no cases of SCC in the MGLSc patients diagnosed and treated in our subspecialty clinics over the last 20 years …”
Section: Resultsmentioning
confidence: 99%
“…Circumcision is generally curative in these men, and we have seen no cases of SCC in the MGLSc patients diagnosed and treated in our subspecialty clinics over the last 20 years. 2,6,13 Weight loss was recommended to all patients, but unfortunately was only achieved by two (11%) patients. Patients who successfully lose a significant amount of weight are often troubled by redundant skin folds that can frustratingly create conditions that promote MGLSc.…”
Section: Resultsmentioning
confidence: 99%
“…It is also argued that the distribution of BXO mirrors the areas subject to urine under occlusion, and unlike LS in women, BXO tends to spare the anogenital region, which is shielded from urine by the scrotum. This chronic irritation of susceptible epithelium is considered to be a predisposing factor to the development of BXO …”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…An Italian study reported that in a cohort of 86 men with BXO, 5.8% went on to develop premalignant change or invasive SCC . A recent retrospective review found that 13.6% of patients with BXO had evidence of penile intraepithelial neoplasia . This high figure is possibly attributable to nearly 50% of this cohort being referred by urologists.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation